2019
DOI: 10.1007/s00453-019-00614-4
|View full text |Cite
|
Sign up to set email alerts
|

Turing Kernelization for Finding Long Paths in Graph Classes Excluding a Topological Minor

Abstract: The notion of Turing kernelization investigates whether a polynomial-time algorithm can solve an NP-hard problem, when it is aided by an oracle that can be queried for the answers to bounded-size subproblems. One of the main open problems in this direction is whether k-Path admits a polynomial Turing kernel: can a polynomial-time algorithm determine whether an undirected graph has a simple path of length k, using an oracle that answers queries of size k O(1) ?We show this can be done when the input graph avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Proof of Theorem A.1. We use the result of Jansen, Pilipczuk, and Wrochna [20] who gave a polynomial Turing kernel for the Longest Path problem in H-topologicalminor-free for every fixed H. That is, they showed how to solve Longest Path in H-topological-minor-free graphs by a polynomial-time algorithm that has access to an oracle solving the problem on H-topological-minor-free graphs which have \ell \scrO (1) vertices.…”
Section: Conclusion and Further Researchmentioning
confidence: 99%
“…Proof of Theorem A.1. We use the result of Jansen, Pilipczuk, and Wrochna [20] who gave a polynomial Turing kernel for the Longest Path problem in H-topologicalminor-free for every fixed H. That is, they showed how to solve Longest Path in H-topological-minor-free graphs by a polynomial-time algorithm that has access to an oracle solving the problem on H-topological-minor-free graphs which have \ell \scrO (1) vertices.…”
Section: Conclusion and Further Researchmentioning
confidence: 99%
“…Proof. We first recall that Jansen et al [19] gave a polynomial Turing kernel for the Longest Path problem in H-topological-minor-free, for every fixed H. That is, they showed how to solve Longest Path in H-topological-minor-free graphs by a polynomial-time algorithm that has access to an oracle solving the problem on H-topological-minor-free graphs which have O(1) vertices.…”
Section: B Problems Definitionsmentioning
confidence: 99%
“…More than ten years ago Binkele-Raible et al [2] found the first problem, namely leaf out-tree(k), which has a polynomial Turing compression but does not admit a polynomial compression unless coNP ⊆ NP/poly. However, by now, people only found limited problems of this kind [1,3,6,14,15,16,17,19].…”
Section: Introductionmentioning
confidence: 99%